Using the subcutaneous route in clinical practice - Galriça Neto, Isabel (2008)
Chronic and palliative patient care must be comfort-centred, and reduction of suffering must be an effective care goal. In this clinical context, an alternative to the oral route, for administration of drugs and fluids is required, in order to reduce suffering and inpatient admissions. Subcutaneous administration of fluids and drugs is an excellent choice, often still ignored in our country. In this article we review the main benefits and characteristics of the use of the subcutaneous route.